Mosaic genome evolution in a recent and rapid avian radiation. Issue 12 (December 2017) - Stryjewski, Katherine; Sorenson, Michael
Abstract Recent genomic analyses of evolutionary radiations suggest that ancestral or standing genetic variation may facilitate rapid diversification, particularly in cases involving convergence in ecological traits. Likewise, lateral transfer of alleles via hybridization may also facilitate adaptive convergence, but little is known about the role of ancestral variation in examples of explosive diversification that primarily involve the evolution of species recognition traits. Here, we show that genomic regions distinguishing sympatric species in an extraordinary radiation of small finches called munias (genusLonchura ) have phylogenetic histories that are discordant with each other, with the overall pattern of autosomal differentiation among species, and with sex-linked and mitochondrial components of the genome. Genome-wide data for 11 species sampled in Australia and Papua New Guinea indicate substantial autosomal introgression between sympatric species, but also identify a limited number of divergent autosomal regions, several of which overlap known colour genes (ASIP,  EDN3, IGSF11,  KITLG, MC1R and SOX10 ). Phylogenetic analysis of these outlier regions shows that different munia species have acquired unique combinations of alleles across a relatively small set of phenotypically relevant genes. Our results demonstrate that the recombination of ancestral genetic variation across multiple loci may be an important mechanism for generating phenotypic novelty and diversity. Munias are small birds that underwent a rapid radiation in Papua New Guinea and Australia. Here, the authors show that the unique colouration of each species was generated by introgression and selection of ancestral genetic variation at a few relevant genes.